2018
DOI: 10.1128/msystems.00236-18
|View full text |Cite
|
Sign up to set email alerts
|

Using Core Genome Alignments To Assign Bacterial Species

Abstract: With the increasing availability of genome sequences, we sought to develop and apply a robust, portable, and high-resolution method for the assignment of genera and species designations that can recapitulate classically defined taxonomic designations. Using cutoffs derived from the lengths and sequence identities of core genome alignments along with phylogenetic analyses, we sought to evaluate or reevaluate genus- and species-level designations for diverse taxa, with an emphasis on the order Rickettsiales, whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 83 publications
4
49
0
1
Order By: Relevance
“…Indeed, the digital DNA-DNA hybridization (DDH) [39] higher than 70 indicates that the two strains might belong to the same species (see Methods). The current analysis indicates only wOo with wOv and wMel with wCau having a dDDH higher than 70, representing the same Wolbachia species, as previously suggested [40].…”
Section: Multi-locus Phylogenies and Phylogenomicssupporting
confidence: 83%
See 1 more Smart Citation
“…Indeed, the digital DNA-DNA hybridization (DDH) [39] higher than 70 indicates that the two strains might belong to the same species (see Methods). The current analysis indicates only wOo with wOv and wMel with wCau having a dDDH higher than 70, representing the same Wolbachia species, as previously suggested [40].…”
Section: Multi-locus Phylogenies and Phylogenomicssupporting
confidence: 83%
“…(which remains problematic for bacteria [40] Figure S9; Additional file 16, Figure S10). To avoid any confusion, we propose not to reuse the supergroup R [27] Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…3 and Additional file 4. Previous research has shown that the dDDH species cutoff (70%) is generally more stringent than the ANI species cutoff (95%~96%) [55]. Considering the intricacies of BCC taxonomy, we used the 70% dDDH (0.0361 for the recommended GGDC setting) and upper boundary 96% ANI (0.04 for the genome distance) thresholds to reclassify the BCC strains for species delineation, which divided 116 strains into 38 clusters and 36 clusters, respectively.…”
Section: Bcc Species Demarcation Based On Dddh and Animentioning
confidence: 99%
“…In fact, almost every Wolbachia 16S amplicon and sequence attributed to A. gambiae is unique, and their diversity spans at least two Wolbachia supergroups (genetic lineages roughly equivalent to species in other bacterial genera, Fig. 3) (40). In combination, we interpret the very low titers and the conflicting phylogenetic affiliations of the sequenced strains as incompatible with the notion of a stable, intraovarially-transmitted Wolbachia symbiont in A. gambiae .…”
Section: Molecular Evidence For Natural Wolbachia In Anopheles Gambiaementioning
confidence: 99%